Impact of Conservation Tillage on Soil Aggregation, Cracking and Bypass Flow in Vertisols of Central India - and Jyothi Raghuwanshi, Sangeeta Lenka, N.K. Lenka, R.K. Singh, R.C. Singh, K.M. Hati, B.L. Lakaria (Journal of the Indian Society of Soil Science, 2014)
This paper investigates the effects of selected conservation tillage systems compared with conventional tillage after six cropping seasons on soil aggregation, crack parameters and the net loss of water through bypass flow in the Vertisols of central India. The experiment on soybean-wheat cropping system was initiated with soybean crop during kharif 2008 with three tillage treatments namely, (1) no-tillage (NT), (2) reduced tillage (RT) and (3) conventional tillage (CT). After six cropping seasons, the effect of tillage treatments was significant on soil aggregation and crack parameters. The mean weight diameter (MWD) and water stable aggregates (WSA) were significantly higher under NT than CT in the 30 cm soil depth. In the 0-5 cm soil depth, the MWD under CT was 0.59 mm compared to 0.87 mm under NT. However, the conservation tillage practices showed a higher crack width and crack volume and thus caused greater loss of water through bypass flow compared with conventional tillage. The data showed that 43-68% of water applied was lost through bypass flow under NT compared to 26-43% under RT and the least, 20-23% under CT, when computed from below 60 cm soil depth. Thus, the trade-offs, between benefits of conservation tillage practices and the higher loss of water through bypass flow should be taken into account while promoting substitution for conventional tillage in Vertisols of central India.